Natural Area Weeds: Distinguishing Native and Non-Native "Boston Ferns" and "Sword Ferns" (Nephrolepis spp.): SSAGR22/AG120, 12/2017 - Langeland, K.A.; Enloe, S.F. (EDIS, 2017)
The proliferation of non-native Nephrolepis fern species in Florida's natural areas poses a significant challenge for distinguishing them from native sword ferns (Nephrolepis exaltata) and giant sword ferns (Nephrolepis biserrata). This fact sheet examines the invasive tuberous sword fern (Nephrolepis cordifolia) and Asian sword fern (Nephrolepis brownii), which resemble native species but disrupt local ecosystems. The document provides identification tools including morphological contrasts, a dichotomous key, and detailed images. Key characteristics such as tuber presence, scale coloration, pinnae arrangement, and indusia shape aid in species differentiation. Control measures including herbicide use and disposal guidelines are also outlined to manage these invasive ferns effectively.